Prevention Strategies: New Departures A Union Perspective - Wilson, Ross (Victoria University of Wellington Law Review, 2004)
This paper provides a trade union perspective on the changes to the New Zealand statutory framework for injury prevention during the 1990s, in the context of the political, social and economic environment of the time, and the measures taken since the election of the Labour led government in 1999 to legislate employee rights, foster applied injury programmes on an industry basis, and to acknowledge injury prevention as a community responsibility. It concludes that these "new departures" are essentially those identified by the Woodhouse Royal Commission in 1967.